Osseointegration of machined and anodized implants under the influence of nicotine - LINDEN,Maria Salete Sandini (2016)
ABSTRACT Objective The objective of this experimental study was to evaluate, through bone densitometry, the performance of two factors that may influence the osseointegration process: nicotine and superficial texturization of the implants. Methods Nineteen New Zealand rabbits (Oryctolagus cuniculus) were randomly distributed in two groups (test and control), in which 38 implants were placed. 19 machined implants (flat) 3.75 mm of diameter by 6.0 mm length were placed at the right tibia of the animals and, at the left tibia, 19 anodized implants (Vulcano(r)) with the same dimensions. Subcutaneous injections of nicotine 3ml/day/kg, three times a day were administered in group, group control also received, three times a day, subcutaneous solution of NaCl (3ml/day/kg), for 8 weeks. After this period, the densitometry analysis was performed. Results Considering the optical density (pixels), there were no statistical significant differences between the types of implants (p = 0.135) as well as between groups (p=0.590). Conclusion The nicotine inside the experimental conditions used in this study and the superficial texturization of the implants indicated that they were not influencing bone density.